2012
DOI: 10.1177/0883073812446162
|View full text |Cite
|
Sign up to set email alerts
|

Development of Children With Symptomatic Intracranial Hemorrhage Born After Vacuum Extraction

Abstract: Vacuum extraction significantly reduces perinatal morbidity/mortality. Increased occurrence of intracranial hemorrhage has been associated with vacuum extraction and is multifactorial; a causative effect is not assumed. Long-term developmental outcome data in this specific subpopulation are lacking and may differ from non-vacuum extraction-associated intracranial hemorrhage. Long-term follow-up of children with symptomatic vacuum extraction-associated intracranial hemorrhage was retrospectively analyzed using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Nine studies reported on intellectual disability after term stroke . The prevalence of intellectual disability was 0% to 88% (median 32.5%).…”
Section: Resultsmentioning
confidence: 99%
“…Nine studies reported on intellectual disability after term stroke . The prevalence of intellectual disability was 0% to 88% (median 32.5%).…”
Section: Resultsmentioning
confidence: 99%
“…Despite the risk of neonatal cerebral complications, few studies have investigated the association between VE on long‐term consequences, and there is a need for more evidence. 16 Previous studies on VE have limitations of small sample size and retrospective design, with no comparison made between complications in VE and ECS deliveries. Further, the use of VE has decreased in some countries in favor of ECS.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Depending on the population studied and the types of bleeds, reported incidence of symptomatic ICH varies from approximately 3-4/10 000 to 10-25/10 000 newborns, [3][4][5][6] with the highest incidence after sequential use of instruments when the first method has failed. 1,2 Depending on the population studied and the types of bleeds, reported incidence of symptomatic ICH varies from approximately 3-4/10 000 to 10-25/10 000 newborns, [3][4][5][6] with the highest incidence after sequential use of instruments when the first method has failed.…”
Section: Introductionmentioning
confidence: 99%
“…Intracranial hemorrhage (ICH) is a rare but potentially life-threatening complication among term newborns, associated with increased risk of long-term neurological disability. 1,2 Depending on the population studied and the types of bleeds, reported incidence of symptomatic ICH varies from approximately 3-4/10 000 to 10-25/10 000 newborns, [3][4][5][6] with the highest incidence after sequential use of instruments when the first method has failed.…”
Section: Introductionmentioning
confidence: 99%